Gestão do conhecimento: um modelo para unidades de pesquisa do Ministério da Ciência, Tecnologia, Inovações e Comunicações - Rocha, Micherlangela Barroso (2018)
In the context of Public Administration (PA), Knowledge Management (KM) acquires its own concept and characteristics due to its specificities, such that the GC seeks to help these organizations face new challenges, implement innovative management practices and improve the quality of processes, products and public services for the benefit of the citizen-user and society in general. GC in organizations is implemented and evaluated through processes described in GC Models that allow a deeper understanding of the reality of GC within organizations. From a review of the literature, it is identified that studies containing specific GC models for PA are very limited. Thus, the general objective of this research is to propose a GC model adequate to the Research Units (UP) of the Ministry of Science and Technology, Innovations and Communications (MCTIC) and its specific objectives include studying the GC models in the literature and those that apply to Public Administration (PA) bodies; to relate general components that should be considered in the elaboration of a KM model for PA; describe characteristics peculiar to UP of the MCTIC; to identify the specific components for a GC model for UP of the MCTIC; propose a GC Model for UP of the MCTIC and; to identify possible barriers and facilitating elements for the implementation of the proposed model. In the research are presented several GC Models in order to verify their relevance and applicability to the reality of public organizations. For a better understanding, this research is structured in sections that are linked in an increasing degree of specificity, in which the concepts and foundations of the GC are presented, followed by the insertion of the thematic in the context of the Public Administration. Specifically, this research addresses the MCTIC Research Units, so it is necessary to explain the Ministry and the characterization of its Research Units. The methodology adopted was of the qualitative and descriptive type in which the Content Analysis method was adopted and contemplated a questioning about the GC in a Research Unit of MCTIC, aiming to provide better inputs for the elaboration of the GC Model for Units of MCTIC. The GC Model proposed for UP of the MCTIC included General and Specific Strategic Drivers, GC Enablers, GC Processes executed through the KDSA Cycle, involving the Stakeholders of the Organization, so all these components were inserted in the environment of the UP of the MCTIC.